2013
DOI: 10.1094/cchem-06-12-0075-r
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waxy Rice Moisture Content and Rate of CO2 Injection on Characteristics of Extruded Pellets and Vacuum‐Puffed Yukwa (a Korean Traditional Snack)

Abstract: Extrusion with CO2 injection was developed to simplify the process of producing vacuum‐puffed yukwa (rice snacks). The effects of feed moisture content and CO2 injection on the characteristics of extruded pellets (maximum viscosity and degree of gelatinization) and vacuum‐puffed yukwa (expansion ratio, bulk density, hardness, and color) were investigated. Higher feed moisture increased the size of vacuum‐puffed yukwa and the degree of gelatinization, whereas the maximum viscosity decreased. Maximum viscosity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…When physical blowing agent injection pressure was increased further (>300 kPa), extrudate hardness increased (Koksel & Masatcioglu, 2018). A decrease in extrudate hardness with CO 2 injection has been reported for sorghum-apple pomace blend extrudates (Lohani & Muthukumarappan, 2017) and extruded pellets made from waxy rice (Shen et al, 2013). The findings of these studies indicate that extrudate hardness is not only affected by physical blowing agent type and injection pressure but also affected by raw material used, potentially explaining the differences in extrudate hardness response as a function of gas type (N 2 vs. CO 2 ) and pulse type (red lentil vs. yellow pea).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…When physical blowing agent injection pressure was increased further (>300 kPa), extrudate hardness increased (Koksel & Masatcioglu, 2018). A decrease in extrudate hardness with CO 2 injection has been reported for sorghum-apple pomace blend extrudates (Lohani & Muthukumarappan, 2017) and extruded pellets made from waxy rice (Shen et al, 2013). The findings of these studies indicate that extrudate hardness is not only affected by physical blowing agent type and injection pressure but also affected by raw material used, potentially explaining the differences in extrudate hardness response as a function of gas type (N 2 vs. CO 2 ) and pulse type (red lentil vs. yellow pea).…”
Section: Resultsmentioning
confidence: 85%
“…For extrudates made from red lentil flour, the presence of N 2 caused a statistically significant ( p < 0.05) increase in extrudate hardness, while hardness of extrudates made from yellow pea flour was not substantially affected by physical blowing agents. It has been previously reported that injection pressure of the physical blowing agent substantially affects extrudate hardness (Koksel & Masatcioglu, ; Lohani & Muthukumarappan, ; Shen et al, ). For example, at low physical blowing agent injection pressures (100–300 kPa), extrudates made from yellow pea flour were shown to have hardness values similar to those of extrudates produced by conventional extrusion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations